Thin film sensing in a planar terahertz meta-waveguide. (1st June 2022) - Islam, Maidul; Kumar Bhowmik, Bhairov; Dhriti, K M; Minakshi,; Mohan, Devendra; Ahmad, Amir; Kumar, Gagan
Abstract: In this paper, we explore the sensing characteristics of a terahertz meta-waveguide consisting of a one-dimensional array of periodically arranged sub-wavelength scale split-ring resonators (SRRs). The substrate of the meta-waveguide structure has two layers. The lower one is made of metal, whereas the upper layer is made of a dielectric. On top of it, metallic SRRs are placed. The meta-waveguide is capable of guiding the fundamental as well as the higher-order terahertz modes along the designed structures. We analyze the sensing capability of the meta-waveguide by covering it with a thin film analyte. The waveguide transmission properties are observed for varying refractive indices of the analyte. Different sensing parameters such as frequency shift, sensitivity, and figure of merit (FoM) of resonance modes supported by the meta-waveguide have been studied. The obtained values of sensitivity and FoM indicate a better sensing capability of the meta-waveguide rather than metamaterial-based structures in the transmission approach. We also employ a coupled harmonic oscillator model in order to interpret and validate the numerical observations. The meta-waveguide design can open alternate avenues for sensing thin film analytes with greater sensitivity.